Causal role of immune cells in thyroid cancer: a two-sample Mendelian randomization study - Shurong Wang; Zhouyu Fang; Wenjin Xiao; Ying Xie; Yueyue Zhang; Zhihua Liu (Discover Oncology)
Abstract Background Immune cells play a crucial role in the progression of thyroid cancer. However, previous research on the link between immune cells and thyroid cancer has produced conflicting results. Methods Based on the public available genome-wide association studies summary statistics, we performed a two-sample Mendelian randomization (MR) to evaluate the causal association between 731 immune phenotypes (including median fluorescence intensities, absolute cell counts, relative cell counts, and morphological parameters) and thyroid cancer. The inverse variance weighting method was employed to investigate the causal relationship between exposure and outcome. Moreover, multiple sensitivity analyses, such as MR-Egger, weighted median, and MR-PRESSO, were simultaneously applied to reinforce the final results. Results After false discovery rate correction, four immunophenotypes were found to be significantly associated with a decreased risk of thyroid cancer. And six immunophenotypes were significantly associated with an increased risk of thyroid cancer. Conclusions Our study has demonstrated the close connection between immune cells and thyroid cancer by genetic means, thus providing guidance for future clinical research.